Serum IDO1 and Biochemical Markers Correlation in Iraqi Women with Breast Cancer - Addai Ali, Hanaa; Mueen Hassoun, Safaa; Adday Ali, Rawaa; Alkadhim Abd, Maha Abd; Saleh Mashkour, Muthana; Majeed, Mohauman Mohaummed (Asian Pacific Journal of Cancer Care, 2025)
Background: Breast cancer (BC) is the leading cause of cancer-related mortality among women worldwide. The type of BC depends on the specific breast cells undergoing malignant transformation and can originate in different regions of the breast. Indoleamine 2,3-dioxygenase 1 (IDO1) is an enzyme that catabolizes tryptophan and is overexpressed in several metastatic tumors, suggesting its potential role in cancer progression. This study aimed to assess serum IDO1 levels across different stages and ages in Iraqi women with BC, evaluating its diagnostic and prognostic value. Additionally, the correlation between IDO1 and clinicopathological features, as well as lipid and liver enzyme profiles, was examined. Materials and Methods: A case-control study was conducted on 90 newly diagnosed Iraqi women with BC and 90 age-matched healthy controls. Serum IDO1 concentrations were measured using enzyme-linked immunosorbent assay (ELISA). Lipid profiles and liver enzyme activities (ALT, AST, ALP) were also evaluated. Statistical analyses were performed using SPSS software. Results: Serum IDO1 levels were significantly elevated in BC patients compared to healthy controls (19.25 ± 7.36 vs. 2.16 ± 0.34 pg/mL; p < 0.001), with levels increasing progressively across advanced disease stages. Patients also exhibited elevated ALT, AST, ALP, triglycerides, total cholesterol, LDL-C, and VLDL-C, along with reduced HDL-C compared to controls. Serum IDO1 showed significant positive correlations with age, ALT, AST, ALP, TG, TC, and HDL-C, but not with BMI, LDL-C, or VLDL-C. Diagnostic performance analysis revealed a cut-off value of 12.65 ng/mL for IDO1, with 80.0% sensitivity, 81.1% specificity, and an AUC of 0.867 (95% CI: 0.814–0.919; p < 0.001). Conclusion: Elevated serum IDO1 is a significant predictor of BC outcomes and may reflect its role in disease pathogenesis. IDO1 demonstrates strong potential as a diagnostic and prognostic biomarker, as well as a promising target for immunotherapeutic strategies in breast cancer management.